2001
DOI: 10.3354/cr017063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on soil frost under snow cover in a forested landscape

Abstract: This study was aimed at assessing the potential impacts of climate change on the depth and duration of soil frost under snow cover in forests growing at different geographical locations in Finland. Frost simulations using a process-based forest ecosystem model (FinnFor) were made for Scots pine Pinus sylvestris L. stands (height 17 m, stand density 1100 stems ha -1 ) growing on a moraine sandy soil. The climate change forecast used in the computations was based on the global ocean-atmosphere general circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 14 publications
7
74
0
Order By: Relevance
“…The results of the snow model also indicated a decrease in snow water equivalent, while the amount of precipitation increased. Similar results have been reported previously [44,48,65,66]. The large predicted increase in temperature, particularly during winter and spring, had a great impact on recharge pattern during 2071-2100.…”
Section: Discussionsupporting
confidence: 79%
“…The results of the snow model also indicated a decrease in snow water equivalent, while the amount of precipitation increased. Similar results have been reported previously [44,48,65,66]. The large predicted increase in temperature, particularly during winter and spring, had a great impact on recharge pattern during 2071-2100.…”
Section: Discussionsupporting
confidence: 79%
“…In accordance with previous studies (Venäläinen et al, 2001a(Venäläinen et al, , 2001bKellomäki et al, 2010), our results suggest that climate warming will lead to shorter soil frost periods reducing wintertime ground-bearing capacity. The projected decrease in the wintertime bearing season length was similar in the studied two climate model ensembles.…”
Section: Evaluations Of Main Results and Their Implications To Forestsupporting
confidence: 81%
“…The climate warming is expected to be pronounced on high latitudes like in Finland (Räisänen and Ylhäisi, 2015;Ruosteenoja et al, 2016). Previous studies have indicated that the climate warming leads unsurprisingly to reduced soil frost depth and shorter soil frost periods (Venäläinen et al, 2001a(Venäläinen et al, , 2001bKellomäki et al, 2010;Jungqvist et al, 2014). This may shorten the winter harvesting season with good ground-bearing capacity, particularly on drained peatlands, having thus mainly negative impact on the forestry sector.…”
mentioning
confidence: 99%
“…According to earlier studies, the decrease in soil frost and snow cover in Finland is probably the largest in the early winter, but also in springtime (March-April) (Peltola et al 1999, Venäläinen et al 2001a. Snow cover slows the freezing of the soil due to the insulation, but on the other hand climate warming has also been stated to increase soil freezing because the climate may become drier and the amount of snow on the ground would be smaller (e.g.…”
Section: Introductionmentioning
confidence: 99%